Infectious Keratitis: An Update on Role of Epigenetics - Verma, Sudhir; Singh, Aastha; Varshney, Akhil; Chandru, R. Arun; Acharya, Manisha; Rajput, Jyoti; Sangwan, Virender Singh; Tiwari, Amit K.; Bhowmick, Tuhin; Tiwari, Anil (Frontiers in Immunology, 2021)
Epigenetic mechanisms modulate gene expression and function without altering the base sequence of DNA and they are reversible, heritable, and get influenced by the environment. Epigenetics has gained momentum and become an increasingly important area of biomedical research in recent past. Epigenetic modifications influence common pathologic responses including inflammation, ischemia, neoplasia, aging, and neurodegeneration. Importantly, epigenetic mechanisms may have a pathogenic role in many complex eye diseases such as corneal dystrophy, cataract, glaucoma, diabetic retinopathy, ocular neoplasia, uveitis, and age-related macular degeneration. Focusing on the epigenetic mechanisms in ocular diseases may provide new understanding and insights into the pathogenesis of complex eye diseases and aid in the development of novel treatments for these diseases. In this review article we will summarize the clinical perspective of infectious keratitis, epigenetics of infectious keratitis, therapeutic potential of epigenetic modifiers and the future perspective.